Phylogeography and Ecological Niche Modeling Reveal Reduced Genetic Diversity and Colonization Patterns of Skunk Cabbage (Symplocarpus foetidus; Araceae) From Glacial Refugia in Eastern North America - Kim, Seon-Hee; Cho, Myong-Suk; Li, Pan; Kim, Seung-Chul (Frontiers in Plant Science, 2018)
Alternating glacial and interglacial periods during the Quaternary have dramatically affected the distribution and population genetic structure of plant and animal species throughout the northern hemisphere. Surprisingly, little is known about the postglacial recolonization history of wetland herbaceous perennials that are widely distributed in the understory of deciduous or mixed deciduous-evergreen forests in eastern North America. In this study, we investigated infraspecific variation among 32 populations of skunk cabbage, Symplocarpus foetidus, to test the hypothesis that the extant species diversity of skunk cabbage is the result of a postglacial range expansion from southern refugia during the Quaternary Ice Age. A total of 4041 base pairs (bp) of the chloroplast intergenic spacer region (cpDNA) was sequenced from 485 individuals sampled from glaciated (18 populations, 275 individuals) and unglaciated (14 populations, 210 individuals) regions east and west of the Appalachian Mountains. Haplotype number, haplotype diversity, and nucleotide diversity were calculated, and genetic variation within and among populations was assessed by analysis of molecular variance (AMOVA). The geographic pattern of genetic differentiation was further investigated with a spatial analysis of molecular variance (SAMOVA). A total of eight haplotypes and three genetic groups (SAMOVA) were recovered and a much higher haplotype number (eight haplotypes) and haplotype diversity (0.7425) was observed in unglaciated compared to glaciated populations (five haplotypes, haplotype diversity = 0.6099). All haplotypes found in glaciated regions represented a subset of haplotypes found in unglaciated regions. Haplotypes of S. foetidus likely diverged during the Tertiary (mid-Miocene and late Pliocene), predating the last glacial maximum (LGM). Predictions based on ecological niche modeling (ENM) suggested that there was considerably less suitable habitat for skunk cabbage during the LGM, and the habitat range was further south compared to the current distribution. Reduced variation and a subset of haplotypes in glaciated regions suggest a founder effect associated with range expansion via long-distance seed dispersal. Our results do not support the “Driftless Area” scenario for the northern refugium, rather the data suggest a “Northeastern” refugium near the southernmost extent of the LGM.